Viable fertilizer prescription model: Soil test crop response approach for sustained and targeted yield, quality of Coriander (Coriandrum sativum L.) in Alfisols - Krishna Murthy Rangaiah; Bhavya Nagaraju; Govinda Kasturappa; Shivakumara Maragondanadibba Nanjundappa; Sanjay Srivastava; Pradip Dey; Immanuel Chongboi Haokip (PLoS ONE, 2026)
A comprehensive three-year field study was conducted to develop and validate soil test crop response (STCR)–based nutrient prescription equations for coriander (Coriandrum sativum L.) in Alfisols. The research comprised three distinct experimental phases: a fertility gradient experiment, a main experiment, and a validation trial. Across these phases, over 72 soil and plant samples were collected and analyzed for nutrient content and compositional quality. The fertility gradient experiment established significant variability in soil NPK status using fodder maize as an indicator crop. In the main experiment, coriander plots subjected to varying fertility levels and nutrient management strategies—including farmyard manure (FYM) supplementation—were assessed for yield, nutrient uptake, and key quality metrics (total phenols, flavonoids, and ascorbic acid). Prescription equations targeting specific yield levels were developed by calculating nutrient requirements and quantifying contributions from soil, fertilizer, and FYM. The validation trial demonstrated that STCR-based recommendations, especially those integrating 7.5 t ha ⁻ ¹ FYM, substantially improved green foliage yield (up to 56.9% higher), nutrient uptake (N, P, K), and quality parameters compared to generalized recommended doses and soil fertility rating approaches. Enhanced outcomes were observed for value cost ratio, response yield stick, and nutrient use efficiency indices (Partial Factor Productivity, Agronomic Efficiency, Partial Nutrient Balance, Internal Utilization Efficiency). Overall, the STCR approach with integrated nutrient management proved effective in increasing yield, improving quality, and optimizing nutrient use efficiency in coriander, advancing the case for site-specific and balanced fertilizer application in sustainable coriander production.